Analisis Model Pembelajaran STEAM dalam Meningkatkan Kemampuan Berpikir Kritis Siswa Sekolah Dasar - Mansyur, Madaliyah Izah; Sumarno, Sumarno; Dwijayanti, Ida (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2024)
This paper aims to provide the benefits of STEAM-related knowledge to help improve the critical thinking skills of elementary school students. The method used is a literature study, utilizing data collection from sources such as books and relevant journals. To fulfill these skills, it is necessary to develop a learning model by utilizing knowledge and technology. STEAM is one of the project-centered learning models based on real-world problems and is a multidisciplinary learning approach integrated to foster and improve the realization of the objectives of the self-learning curriculum designed in accordance with 21st-century skills. The results in this paper indicate that the STEAM learning model can significantly enhance the critical thinking skills of elementary school students by engaging them in activities that require problem-solving, creativity, and collaboration. Implementing STEAM in classrooms encourages students to connect their learning to practical, real-life contexts, thereby promoting deeper understanding and retention of knowledge.